Synthesis, characterization and evaluation of antidiabetic activity of novel indoline derivatives (Bangladesh Journal of Pharmacology, 2017)
Series of indoline derivatives were synthesized using N-(4-aminophenyl)indoline-1-carbothiamide as a precursor. The confirmation of synthesized compounds was done by 1H-NMR, 13C-NMR, LC-MS (ESI) and FT-IR. In vitro antidiabetic activity of synthesized indoline derivatives were examined by standard ?-amylase inhibition assay. The compounds 4a (IC50 = 52.1 µg/mL) and 4b (IC50 = 57.7 µg/mL) showed potent ?-amylase inhibition activity. The compounds 3a (IC50 = 62.2 µg/mL) and 3b (IC50 = 60.7 µg/mL) showed moderate antidiabetic activity.Video Clip of Methodology:19 min 21 sec   Full Screen   Alternate